Effectiveness of Theraplay on Reactive Attachment Disorder in Children Aged 8-12 Years - Sadeghi Amrabadi, Zohre; Esteki, Mahnaz; Pooshneh, Kambiz; Salehi, Mahdieh (Applied Family Therapy Journal (AFTJ), 2022)
Aim: The aim of this study was to determine the effectiveness of attachment-based play therapy method (Thera-play) on reactive attachment disorder in children aged 8 to 12 years. Method: The research method was quasi-experimental with pre-test, post-test and follow-up design. The statistical population included all children aged 8 to 12 years in Tehran who had expressed interest in the call through cyberspace. From the mentioned community, 32 children were selected and divided into two groups of experiments and controls. The intervention was presented as a weekly attachment-centered play therapy (Thera-play) (Peacock, 2020). Participants completed the Attachment Disorder Questionnaire (Randolph, 2000) before the beginning and after the sessions and repeated the post-test three months later. Data were analyzed by SPSS software using two-factor ANOVA statistical method. Results: The results of data analysis confirmed the significant effect of attachment-centered play therapy (Thera-play) on the symptoms of reactive attachment disorder (antisocial behaviors, impulsivity and coercion) (P